Deskripsi Hasil Uji Angka Lempeng Total (ALT) Pada Beberapa Susu Formula Bayi - Puspandari, Nelly; Isnawati, Ani (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2015)
Infant formula is the nutrient source for some babies who were not breastfed. Risk factors for infection in infants less than 6 months old who consume formula are greater than those who were breastfed. This is due to the baby's immune system is not well formed. Therefore, it is important to supervise formula safety more strict than adult’s food. Total plate count (TPC) is one of the factors considered in the infant formula. The aim of this study is to define safety of infant formula based on total plate count within infant formula distributed in Indonesia in 2011. The study was a cross sectional study. The samples were representative of infant formula distributed in 23 province. Total plate count method and interpretation were conducted based on ISO/TS 22964. The TPC of each samples were examined three times. The TPC of all infant formulas were below of SNI breakpoint, which is less than 104cfu/gram. TPC ranged from